Fluctuating asymmetry of Betula pendula Roth leaves – an index of environment quality - Franiel, Izabella (Biodiversity: Research and Conservation, 2008)
Fluctuating asymmetry (FA) is a non-specific stress indicator and describe developmental instability in bilateral structure. In plants, FA has been used as a tool for monitoring levels of ecological stress, however, in trees, high value of leaf FA has been assumed to indicate the level of environmental stresses. In this work, I analyzed the FA response to abiotic stress in the Betula pendula Roth leaves in two contrasting sites (polluted vs unpolluted). I also investigated whether another biometrical leaf feature is able to determine FA as an environmental stress indicator. After the cluster analysis and mixed-model ANOVA, I selected one feature, which was leaf apical angle. Results showed significant differences (using chi square test) in apical angle FA in the unpolluted site as compared to the polluted one. Concluding, I suggested that plants living in more stressful sites are more symmetrical and leaf FA for plant species with a wide ecological distribution such as Betula pendula should be used as an index of environmental quality.